Les marges renaissantes : Amazigh, Juif, Noir. Ce que la révolution a changé dans ce « petit pays homogène par excellence » qu’est la Tunisie - Stéphanie Pouessel (L’Année du Maghreb)
This article considers the claims made by a number of “minority” groups as a groundswell sweeping the official “cultural monolithic nature” of postdictatorial Tunisia. A focus on citizens who assert themselves on the cultural and political scene as members of minority groups (Amazigh, black, Jewish) helps understand how they attempt to place the issue of ethnic and religious plurality in Tunisian society at the center of public debate. The recognition of “cultural diversity” thus plays a significant part in the political stakes following the events of January 14, 2011 and the first democratic elections to form a Constituent Assembly. The phase of remodeling of the “nation’s” representations leads to the emergence of new insights on discrimination, recognition or plural memory : where does the Jewish heritage stand in a country dominated by political Islam ? Why include the fight against racial discrimination in the new constitution ? Finally, how can Tunisian Amazigh specificity develop under pressure from pan-Maghreb Amazigh activism ?